2021
DOI: 10.3389/fnins.2021.650219
|View full text |Cite
|
Sign up to set email alerts
|

A Dissociation of Attention, Executive Function and Reaction to Difficulty: Development of the MindPulse Test, a Novel Digital Neuropsychological Test for Precise Quantification of Perceptual-Motor Decision-Making Processes

Abstract: Traditionally, neuropsychological testing has assessed processing speed and precision, closely related to the ability to perform high-order cognitive tasks. An individual making a decision under time pressure must constantly rebalance its speed to action in order to account for possible errors. A deficit in processing speed appears to be afrequent disorder caused by cerebral damage — but it can be hard to pinpoint the exact cause of the slowdown. It is therefore important to separate the perceptual-motor compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…According to the free energy theory, the brain seeks to minimize uncertainty and resist disorder by reducing the uncertainty of upcoming events [39], which contributes to decreasing task complexity. Coincidently, it is reported that task complexity influences motor responses [40], more complex tasks (such as completing complex rhythmic finger-tapping [41]) lead to increased beta-ERD ipsilateral activation, and correspondingly decrease motor-related interhemispheric differences. In addition, predictability enhanced the contralateral motor area ERD during motor preparation [42].…”
Section: Discussionmentioning
confidence: 96%
“…According to the free energy theory, the brain seeks to minimize uncertainty and resist disorder by reducing the uncertainty of upcoming events [39], which contributes to decreasing task complexity. Coincidently, it is reported that task complexity influences motor responses [40], more complex tasks (such as completing complex rhythmic finger-tapping [41]) lead to increased beta-ERD ipsilateral activation, and correspondingly decrease motor-related interhemispheric differences. In addition, predictability enhanced the contralateral motor area ERD during motor preparation [42].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies with process-based training have shown relative stability and minor training effects in the far transfer effects of EF training [ 32 ]. Therefore, the psychomotor speed, as the indicator of the far transfer effects, was assessed using the auditory-visual reaction time test (model 32020 A, Lafayette instrument, US) [ 33 ] and finger tapping test (Torrance, CA 90503-5124) [ 28 ]. Previous studies have supported the reliability and validity of these tests [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have supported the reliability and validity of these tests [ 34 , 35 ]. The auditory-visual reaction time test measured the time interval between the appearance of the stimulus (light, sound) and voluntary finger response [ 33 ]. The finger tapping test was used to assess psychomotor speed and it asked the participant to tap the tip of the index finger in rapid succession from a height of 15 centimeters 10 times [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac vagal activity would also constitute a measure of the efficiency of an individual's executive functioning. Recently, a new neurocognitive test was developed and named "MindPulse" (39). The purpose of this test is to highlight the elements underlying perceptual-motor decision-making, in particular attentional and executive functions.…”
Section: Cognitive Influence On Adaptationmentioning
confidence: 99%